An Empirical Evaluation of Trade Effect of CEPA between Mainland China and Hong Kong - DU, Qinghao (The Graduate School, Ajou University, 2010)
It has been six years since Hong Kong CEPA (a free trade agreement signed between Mainland China and Hong Kong) came into effect on Jan 1st, 2004. Some serious questions, like about the trade effects of CEPA, or which side exactly got significant benefit from CEPA, attracted lots of attention from policy makers and general businessmen. In order to answer these questions, this thesis will concentrate on evaluating the trade effect of CEPA by making use of Balassa Economic Model, the theory of trade creation and trade diversion and OLS econometric analysis model. In addition, this study can be distinguished from others because it uses quantitative methods and long periodic consecutive economic data to run regressions, provideing a detailed and scientific analysis of the contribution and effect of CEPA not only on Hong Kong, but also on Mainland China. The result of this study shows that CEPA has a significant positive effect for both Mainland China and Hong Kong since it took effect. More specifically, it played a positive role for the intra-regional (between Mainland China and Hong Kong) trade; it didn’t bring negative influence for the extra-regional (between Mainland China and other regions or between Hong Kong and other regions) trade; in general, it produced national welfare for both sides.
학위논문(석사)--아주대학 국제대학원--국제통상학과,2010. 8
Keywords: CEPA; free trade; free trade agreement; trade effect